Renal insulin resistance in type 2 diabetes mellitus and progression of chronic kidney disease: potential pathogenic mechanisms. Issue 6 (2nd November 2022) - Alqallaf, Alrataj; Swan, Patrick; Docherty, Neil G
ABSTRACT: Introduction: A bidirectional association exists between insulin resistance (IR) and chronic kidney disease (CKD) in Type 2 Diabetes Mellitus (T2DM). Baseline measures of IR are predictive of CKD progression, and uremia in progressive CKD is itself, in turn, associated with a worsening of IR. Pre-clinical research reveals that intrinsic IR in glomerular podocytes and the renal tubule may serve as a pathogenic driver of CKD in T2DM. Areas covered: The present manuscript takes as its point of departure, the recently identified prognostic utility of severe insulin resistance as a predictor of CKD in T2DM. Findings from a series of studies describing the association of IR with pathological alterations in both established, and less commonly assessed dynamic measures of renal impairment are discussed. Drawing upon the pre-clinical mechanistic evidence base, the cellular and molecular basis of intrinsic renal IR as a promoter of CKD is considered. Expert opinion: Measurement of insulin sensitivity may add value to profiling of renal risk in T2DM. Rational selection of therapeutic strategies targeting the enhancement of insulin sensitivity merits special attention regarding the personalized management of CKD in insulin resistance predominant T2DM.